Formulation of strategies for the implementation of integral management system based on ISO 9001:2015 and 14001:2015 in the company surtiapliques (Bogotá-Colombia) (2023)
Surtiapliques is a Company of the metalworking sector, in this contribution the design of an Integral Management System (IMS) is proposed, employing the Quality Management ISO 9001:2015, emphasizing in tracing and measurement of process, and customer satisfaction; the needed improvements were determined to increase environmental performance, applying Cleaner Production tools (CP) and the standard ISO 14001:2015. This will allow the growth of the company in the industrial sector, contributing to sustainable development. Designed solutions were based on the analysis and operational development, using qualitative, quantitative, and statistical methods, which were inputs for the documental design of the Management System, which pretends standardize processes and increases the effectiveness of business management. In the operational development phase, of quality management, the technical specifications of the products, process sheets and the control charts were built; in so far as an environmental performance, the main aspects and impacts of the company were analyzed, as well as the analysis of occupational risk and strategies for the sustainable management of natural resources, using matrices to assess environmental aspects and Eco-balances and life cycle analysis. Copyright © 2018, AIDIC Servizi S.r.l.